Sleep Quality and Its Correlates Among Medical Students of a Tertiary Care Hospital: A Cross-Sectional Study from Tertiary Health Care Centre in Southern Rajasthan - Singh, Sarvpreet; Agrawal, Tanay; Kumar, Nitin; Agarwal, Bharat; Kumar, Sunil (National Journal of Medical Research, 2025)
Background: Sleep plays a vital role in maintaining physical and mental health, especially among medical students, who often face academic stress, long study hours, and irregular routines. These challenges can compromise sleep quality, affecting academic performance and overall well-being. This study aimed to assess the prevalence of students with poor sleep quality and identify its associated factors among undergraduate medical students in a tertiary care hospital in Southern Rajasthan. Methodology: A cross-sectional study was conducted among 360 undergraduate medical students using a structured questionnaire, including the Pittsburgh Sleep Quality Index (PSQI). Sociodemographic, academic, and lifestyle factors were collected. Data were analyzed using descriptive statistics and chi-square tests to assess associations between sleep quality and potential correlates. A p-value of <0.05 was considered statistically significant. Results: Out of 360 participants, 270 (75%) reported poor sleep quality. Significant associations were found between poor sleep quality and domicile (p=0.015), year of study (p=0.032), sleep duration (p <0.001), screen time (p=0.003), academic performance (p=0.029), and presence of self-reported health problems (p=0.050). Factors such as gender, hostel stay, smoking, alcohol use, and physical activity were not significantly associated with sleep quality. Conclusion: The proportion of poor sleep quality among medical students is alarmingly high. Academic pressure, increased screen time, and inadequate sleep duration were key contributing factors. Interventions promoting better sleep hygiene and stress management are essential to improve the academic performance and mental health of future healthcare professionals.